Synergistic Effect of Sulindac and Simvastatin on Apoptosis in Lung Cancer A549 Cells through AKT-Dependent Downregulation of Survivin - Kim, Young-Suk (Cancer Res Treat, 2015)
PURPOSE: Non-steroidal anti-inflammatory drugs (NSAIDs) and statins are potential chemopreventive or chemotherapeutic agents. The mechanism underlying the deregulation of survivin by NSAIDs and statins in human non-small cell lung cancer cells has not been elucidated. In this study, we investigated the synergistic interaction of sulindac and simvastatin in lung cancer A549 cells. MATERIALS AND METHODS: Cell viability was measured by an MTT assay, while the expression of apoptotic markers, AKT, and survivin in response to sulindac and simvastatin was examined by Western blotting. DNA fragmentation by apoptosis was analyzed by flow cytometry in A549 cells. Reactive oxygen species (ROS) generation was measured by flow cytometry using H(2)DCFDA and MitoSOX Red, and the effects of pretreatment with N-acetylcysteine were tested. The effects of AKT on survivin expression in sulindac- and simvastatin-treated cells were assessed. Survivin was knocked down or overexpressed to determine its role in apoptosis induced by sulindac and simvastatin. RESULTS: Sulindac and simvastatin synergistically augmented apoptotic activity and intracellular ROS production in A549 cells. Inhibition of AKT by siRNA or LY294002 inhibited survivin, while AKT overexpression markedly increased survivin expression, even in the presence of sulindac and simvastatin. Moreover, survivin siRNA enhanced sulindac- and simvastatininduced apoptosis. In contrast, survivin upregulation protected against sulindac- and simvastatin-induced apoptosis. CONCLUSION: Combined treatment with sulindac and simvastatin augmented their apoptotic potential in lung cancer cells through AKT signaling-dependent downregulation of survivin. These results indicate that sulindac and simvastatin may be clinically promising therapies for the prevention of lung cancer.